Genetic Analysis and In Vitro Enzymatic Determination of Bacterial Community in Compost Teas from Different Sources. Issue 4 (2nd October 2018) - Diánez, Fernando; Marín, Francisco; Santos, Mila; Gea, Francisco J.; Navarro, María J.; Piñeiro, Maximino; González, Juan M.
Abstract: Compost tea has been used throughout the world to control diseases and promote the growth of plants. The microbial community is the main factor involved both in the antagonistic effect against relevant phytopathogens and as a stimulator of plant growth. The objective of this research is to determine the bacterial diversity present in four types of compost as well as some of the mechanisms that may be involved in the positive effects of compost tea on crops. Aerated (ACT) and non-aerated (NCT) compost teas were obtained from four different composts: spent mushroom substrate compost (SMC), grape marc compost (GMC), greenhouse horticultural crop residues compost (CRC), and vermicompost (CRV). 16S rDNA-based DGGE profiles were obtained for each compost tea and their respective bacterial communities were analyzed. Of the 100 clones obtained, those typical for being dominant for all profiles were chosen. In total, 20 different clones were sequenced. The results showed that the bacterial communities of most compost teas had high richness, diversity, and evenness values, with relative abundance of species belonging to Bacteroidetes and Proteobacteria . The NCTs obtained from all the composts, especially CRC and CRV, showed high levels of siderophore production, while teas from GMC manifested high and consistent cellulase activity. The ACTs from all the composts, especially SMC, had high protease activity.